CONSUMER-GENERATED ADS ON YOUTUBE: IMPACTS OF SOURCE CREDIBILITY AND NEED FOR COGNITION ON ATTITUDES, INTERACTIVE BEHAVIORS, AND EWOM - Hansen, Sara Steffes; Lee, Jin Kyun; Lee, Shu-Yueh (Journal of electronic commerce research, 2014)
This study examines consumer-generated advertising (CGA) impacts on consumer attitudes, and behaviors for interacting with YouTube features and passing along electronic word-of-mouth. An online experiment with 175 subjects was conducted with a 2x2x2 factorial design. Participants viewed a video advertisement on YouTube, framed as either a consumer-generated or firm-generated advertisement, to determine effects of source credibility with different levels of product involvement. Need for cognition (NFC) also was examined. Analysis revealed consumers as source significantly enhanced advertising attitudes and interactivity behaviors. Higher NFC levels significantly increased interactivity and pass-along. Findings suggest that CGA is a trusted form of user-generated content, with one exposure prompting interactive engagement to search, rate, or comment. Practical implications show potential for online marketers to see positive consumer responses to advertisements labeled as CGA with content flexibility for broad consumer groups, and enhanced pass-along from high-NFC individuals.